1997
DOI: 10.1007/bf02436036
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic index of grain amaranth, wheat and rice in NIDDM subjects

Abstract: Glycemic index of grain amaranth, wheat and rice preparations was studied in non-insulin dependent diabetic subjects. Diets containing 50 g carbohydrate equivalent were given and post-prandial blood glucose estimated at different intervals. Glycemic index calculated for different experimental diets showed that GI of amaranth-wheat composite flour diet (25:75) was the least (65.6%) followed by wheat diet (65.7%), rice diet (69.2%), amaranth-wheat flour 50:50 (75.5%), and popped amaranth in milk (97.3%). Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
3
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 28 publications
1
15
3
1
Order By: Relevance
“…7,8) Diabetes is a major risk factor for premature atherosclerosis, and oxidative stress plays an important role. In fact, diabetic monocytes produce increased superoxide anion (O 2 Ϫ ).…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…7,8) Diabetes is a major risk factor for premature atherosclerosis, and oxidative stress plays an important role. In fact, diabetic monocytes produce increased superoxide anion (O 2 Ϫ ).…”
Section: )mentioning
confidence: 99%
“…5) Recent studies have demonstrated a variety of important and unique nutraceutical type applications for grain amaranth, 6) including its use as an adjunct to lower blood glucose response in non-insulin-dependent diabetics and in other applications to lower blood serum cholesterol levels. 7,8) Diabetes is a major risk factor for premature atherosclerosis, and oxidative stress plays an important role. In fact, diabetic monocytes produce increased superoxide anion (O 2 Ϫ ).…”
mentioning
confidence: 99%
“…Polyphenolic compounds, such as phenolic acids and flavonoids, have been characterized in amaranth grains [6]. In addition to its promising nutritional qualities, amaranth grains are considered to be an important source of food for celiac patients, since they are glu-ten-free [7], diabetic [8], hypercholesterolemic subjects [9,10] and coronary heart disease and hypertension patients [11].…”
Section: Introductionmentioning
confidence: 99%
“…Amaranth exhibits waxy nature, its amylose content is relatively very less compared to other cereals and hence, the functional properties of amaranth starch will be of prominence (Resio and Suarez 2001;Bello-Perez et al 2006). Amaranth starch has been found to have low viscosity, high solubility, and low gelatinization temperature (Chaturvedi et al 1997;Resio and Suarez 2001). The rheological properties of amaranth starch indicated that, the paste contains pseudoplastic and thixotropic behaviour and the flow properties were better than that of maize starch (Teli et al 2007).…”
Section: Introductionmentioning
confidence: 99%